PEMBELAJARAN SAINS MELALUI SURAH AL-NABA' - Herni, Zulfiana (Edudeena : Journal of Islamic Religious Education, 2018)
Abstract :  Learning science at the OLD learning methods are being developed in order to provide children's understanding about the universe and its contents, the study done by the method of conditioning verses to introduce kauniyah as in letter Al-Naba '. This verse tells us how God created the universe and its contents. Thus teaches letter at OLD and as a method of introduction of natural media as a means of learning and enabling children to memorize in order to hone a child's brain. Besides learning on learning science in the OLD and usher protégé to have noble morality and discipline to time for example in memorized the qur'an in verses kauniyah children bound by time and before read using the ablution for the sake of clearing him and facing the Qibla, so accustomed to polite in reading it. Abstrak : Pembelajaran sains pada PAUD adalah metode pembelajaran yang akan dikembangkan demi untuk memberikan pemahaman anak-anak tentang alam semesta dan isinya, pembelajaran ini dilakukan dengan metode pembiasaan mengenalkan ayat-ayat kauniyah seperti pada surah Al-Naba'. Ayat ini menjelaskan bagaiman Allah menciptakan alam semesta dan isinya. Dengan demikian mengajarkan surah ini pada PAUD sebagai metode pengenalan media alam sebagai sarana pembelajaran dan memungkinkan anak untuk menghafalkannya demi untuk mengasah otak anak. Disamping itu pembelajaran pada PAUD dalam pembelajaran sains mengantarkan anak didik untuk mempunyai akhlak yang mulia dan disiplin kepada waktu sebagai contoh dalam menghafalkan Al-quran dalam ayat-ayat kauniyah anak-anak diikat oleh waktu dan sebelum membaca menggunakan wudhu demi membersihkan dirinya dan menghadap kiblat, agar terbiasa sopan dalam membacanya.